Evaluating Fine Arts Students' Attitudes towards Ongoing ESP Programs - Kural, Faruk (CUKUROVA UNIV, 2019)
This research paper is based on the revision and improvement of on-going English for Specific Purposes (ESP) programs developed for undergraduate fine arts students of a private university in Istanbul, Turkey. The programs were originally developed upon request from the faculty administration due to the need felt by lack of adequate English language teaching in the faculty's undergraduate programs where in the new system the candidates were required to comply with only the intermediate level preparatory course requirements to be eligible to pursue their undergraduate programs. The students who had already complied with the previous preparatory school requirements and who attended the undergraduate programs were integrated into the new programs. They were required to take some of the new courses depending on the number of the previous English language courses they had taken - as compulsory non-credit courses. Thus, this paper seeks to identify the attitude the undergraduate students of the Faculty of Fine Arts had towards the two kinds of ongoing programs which had been implemented for six months since their establishment.
Keywords: ESP; Proficiency; Fine arts; Needs analysis; Learner attitudes